Te Atatu Me: A Retrospective - Moon, Paul (Stout Research Centre for New Zealand Studies, 2025)
John B. Turner (b. 1943) is one of New Zealand’s preeminent documentary and art photographers. This article explores a particular collection of images of the west Auckland suburb of Te Atatū Peninsula, which Turner took over a period of seven years (2005-2011), and which were published in the book Te Atatu Me: Photographs of an Urban New Zealand Village (2015). The focus here is on how such photography can contribute to the historical archive as visual evidence through the intersection that it is able to achieve between documenting scenes in the form of photographs, and using the aesthetic dimensions of the medium both to project forms of meaning onto those images and as a device of cultural preservation.
Keywords: 3601 Art history, theory and criticism; 4303 Historical studies